Interaction between the MtDELLA–MtGAF1 Complex and MtARF3 Mediates Transcriptional Control of MtGA3ox1 to Elaborate Leaf Margin Formation in Medicago truncatula. (2nd January 2021) - Wen, Lizhu; Kong, Yiming; Wang, Hongfeng; Xu, Yiteng; Lu, Zhichao; Zhang, Jing; Wang, Minmin; Wang, Xiao; Han, Lu; Zhou, Chuanen
Abstract: The molecular mechanisms underlying the diversity of leaf shapes have been of great interest to researchers. Leaf shape depends on the pattern of serrations and the degree of indentation of leaf margins. Multiple transcription factors and hormone signaling pathways are involved in this process. In this study, we characterized the developmental roles of SMALL AND SERRATED LEAF ( SSL ) by analyzing a recessive mutant in the model legume Medicago truncatula . An ortholog of Arabidopsis thaliana GA3-oxidase 1 ( GA3ox1 ), MtGA3ox1 / SSL, is required for GA biosynthesis. Loss of function in MtGA3ox1 results in the small plant and lateral organs. The prominent phenotype of the mtga3ox1 mutant is a more pronounced leaf margin, indicating the critical role of GA level in leaf margin formation. Moreover, 35S:MtDELLA2 Δ DELLA and 35S:MtARF3 transgenic plants display leaves with a deeply wavy margin, which resembles those of mtga3ox1 . Further investigations show that MtGA3ox1 is under the control of MtDELLA1/2/3–MtGAF1 complex-dependent feedback regulation. Further, MtARF3 behaves as a competitive inhibitor of MtDELLA2/3–MtGAF1 complexes to repress the expression of MtGA3ox1 indirectly. These findings suggest that GA feedback regulatory circuits play a fundamental role in leaf margin formation, in which the posttranslational interaction between transcription factors functions as an additional feature.